Relación de estado nutricional con las afecciones bucodentales en escolares de 4 a 12 años, de la Escuela Fiscal de niños 24 de Mayo del Barrio Pucacocha de la ciudad de Loja en el periodo marzo-julio 2015 - Morocho Valle, Karina Elizabeth (2015)
Nutrition is an elemental requirement from the UN Human Condition, and also the importance of this, the UN development in the PROPER paragraph of the oral cavity, their affected gender status ONU in a protein malnutrition which is accompanied by various clinical manifestations, in some intensity and scalability degrees. This is why, this investigation’s objective is to determine the possible relation between nutritional status and major oral diseases. This is investigation is a descriptive, prospective and transversal study in children from the school “24 de Mayo” from the Pucacocha neighborhood, in a sample of 156 students, where we evaluated the nutritional state through weight, height and body mass (BMI), as well as the main oral diseases through the use of the Dental Clinic History. During the principal results we manage to find, 117 children with a normal nutritional state, 39 with nutritional disorders; 18 with overweight, 6 with obesity, 13 with a risk of malnutrition, and 2 children with malnutrition in relation to the female students which present overweight and obesity. In relation to oral manifestations, we managed to observe a high prevalence of caries, moderate gingivitis in children with malnutrition in an 100% and the slight gingivitis in children with overweight in a 72, 2%. The rash alterations were higher in children at risk of malnutrition in an 84, 6%. The malocclusion were higher on malnourished children with a 100% and an 83, 3% in overweigh children presented in class III. Finally it was advised to develop and implement programs of health/personal hygiene related to oral health and also a healthy diet, in which it’s actions and strategies are straightly directed to children, parents and authorities from the institution. Key words: - Nutritional state, oral affections.